The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1159/000100450
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms in the Lives of Terminal Cancer Patients: Which Is the Most Important?

Abstract: Objectives: Symptoms other than their primary disease can interfere in the lives of terminal cancer patients. We sought to identify which of these symptoms is most important. Methods: We administered a questionnaire, including the M.D. Anderson Symptom Inventory (MDASI), to 142 terminal cancer patients at the National Cancer Center, Korea. The validity of the MDASI was tested by principal-axis factor analysis and Cronbach’s α coefficient. Stepwise multiple regression analysis was used to determine the symptoms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 20 publications
1
16
0
2
Order By: Relevance
“…[34][35][36][37][38][39][40][41] According to two analyses of patients with terminal cancer in varied palliative care settings, fatigue was the most frequently reported symptom, and pain, depression, and anxiety were the most distressing symptoms. 2,42 In this study, the most frequently reported symptoms were pain (58%), dyspnea (52%), constipation (45%), and fatigue (23%).…”
Section: Discussionmentioning
confidence: 99%
“…[34][35][36][37][38][39][40][41] According to two analyses of patients with terminal cancer in varied palliative care settings, fatigue was the most frequently reported symptom, and pain, depression, and anxiety were the most distressing symptoms. 2,42 In this study, the most frequently reported symptoms were pain (58%), dyspnea (52%), constipation (45%), and fatigue (23%).…”
Section: Discussionmentioning
confidence: 99%
“…We based the questionnaire assessing available support and unmet needs on previous studies in the same area [1][2][3][7][8][9], and we pilot tested it on healthy volunteers and family members of cancer patients. Subjects were asked to rate substantial needs of caregivers of terminal cancer patients on a four-point scale ranging from "none at all" to "high" in the following areas: (1) symptom management, (2) psychosocial support, (3) financial support, (4) community support, including volunteer assistance, and (5) religious support.…”
Section: Survey and Data Collectionmentioning
confidence: 99%
“…Caregivers of terminal cancer patients face extraordinary stresses owing to the patients' multiple symptoms [1] and their own psychological suffering [2,3]. Both the patients and their caregivers have important and wide-ranging needs for assistance that are often unmet [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Research on modern terminally ill cancer patients shows that the three most constant and debilitating symptoms are pain, weakness and fatigue, with patients also likely to suffer the following symptoms to varying degrees: shortness of breath, anxiety, depression, lack of appetite, memory problems, vomiting, nausea, numbness/tingling, sleeping problems, restlessness, constipation and anorexia (Kwon et al 2006;Ruijs et al 2013;Jensen et al 2014). While it is not possible to know which of these this man suffered, Kwon et al (2006) found that modern patients had an average of 11 ± 2.5 symptoms, so it is likely he had most if not all of the above symptoms. Any combination of these symptoms would have had the obvious effects of reduced physical activity and eventual muscle atrophy.…”
Section: Diagnosismentioning
confidence: 99%